KAJIAN RANGKAIAN UPACARA KEMATIAN ETNIS TENGGER SEBAGAI DAYA TARIK WISATA DESA ARGOSARI, LUMAJANG - Diana Martalia; Ida Ayu Etsa Pracintya (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2023)
Culture includes various things which are the inheritance or transmission of property, norms, survival habits, rituals, arts, and traditions that are passed down to each generation. The Tengger ethnic group has a unique death ceremony tradition, which makes this tradition have the potential to be developed as a tourist attraction in Argosari Village, Lumajang. The aim of this research was to identify the potential of the Tengger Ethnic death ceremony and the philosophical meaning of this tradition. The research method used was qualitative with an ethnographic approach, where this approach is an approach that aims to describe the culture characteristics of an individual or a group of people. The Results obtained three series of Tengger ethnic death ceremonies, namely: (1) the ceremony that held for the newly death individual (Nyurup Ceremony); (2) the death ceremony on the 11 th day (Sedekah Ceremony); and (3) the most important ceremony large as the peak ceremony of death (Entas-Entas Ceremony). These three series of funeral ceremonies qualify as cultural tourism attractions because these traditions are still passed down from generation to generation, so that their existence can be maintained and enjoyed by tourists with various motivations for visiting.